21. Pseudohyperkalemia due to pneumatic transport in acute lymphocytic leukemia patients: Report of two cases - Mai, Tran Thi Chi; Lan, Bui Ngoc; Uyen, Vu Thi Tu (Tạp chí Nghiên cứu Y học, 2023)
Pseudohyperkalemia occurs occasionally in leukemic patients with excessively elevated white blood cells. Early diagnosis of pseudohyperkalemia is crucial for proper treatment. Increased white blood cell fragility coupled with mechanical trauma may be the causal mechanism. We describe two cases of pseudohyperkalemia caused by mechanical disruption of white blood cells due to pneumatic tube transport of the specimens. In case when the white blood cell is extraordinarily elevated, specimen should be delivered in person instead of using pneumatic tube transport and specimen should be analyzed as soon as possible. Whole blood potassium analysis by blood gas analyzer is more reliable to confirm or rule out pseudohyperkalemia.